Regulation of Leukocyte Recruitment to the Spleen and Peritoneal Cavity during Pristane-Induced Inflammation. (19th October 2017) - Li, Yu; Wu, Junping; Xu, Long; Wu, Qi; Wan, Zhen; Li, Li; Yu, Hongzhi; Li, Xue; Li, Kuan; Zhang, Qiuyang; Hou, Zhili; Sun, Xin; et al.
Abstract : Chronic inflammation is associated with an increased number of leukocytes in the spleen, which are then redirected to the site of inflammation. However, it remains unknown how leukocyte recruitment is regulated. Herein, chronic inflammation was induced by intraperitoneal injection of pristane into mice. Leukocytes in the spleen or in the peritoneal cavity were quantified by flow cytometry. We found that the loss of IL-6 decreased macrophage recruitment to the spleen and the peritoneal cavity during pristane-induced inflammation. The loss of TNF α delayed the recruitment of neutrophils and macrophages to the spleen and inhibited the recruitment of neutrophils, macrophages, B cells, and T cells. The recruitment of neutrophils and macrophages into the spleen or peritoneal cavity was largely inhibited in the absence of LT α . The loss of TNF α receptor 1/2 resulted in reduced recruitment of neutrophils, macrophages, and dendritic cells into the spleen, but only neutrophil recruitment was inhibited in the peritoneal cavity. Similarly, a lack of B cells significantly impeded the recruitment of neutrophils, macrophages, and dendritic cells to the spleen. However, only macrophage recruitment was inhibited in the absence of T cells in the spleen. These data provide insight into the development of chronic inflammation induced by noninfectious substances.